2022
DOI: 10.1002/jcsm.13074
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes is an independent risk factor for sarcopenia in older men, but not in older women: the Bunkyo Health Study

Abstract: Background Sarcopenia is a major cause of disability in the elderly. Although type 2 diabetes is a risk factor for increased sarcopenia, the relationship between prediabetes and sarcopenia has not been elucidated. We aimed to examine the relationship between sarcopenia and prediabetes. Methods The design of this study is a cross‐sectional study. We evaluated glucose metabolism using the 75‐g oral glucose tolerance test and glycated haemoglobin, appendicular skeletal muscle mass, and hand grip strength in 1629 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Few studies had been conducted to investigate the correlation between pre-diabetes and sarcopenia. A recent study conducted in Japan revealed increasing sarcopenia rate in pre-diabetic older men, but not women (21). Focusing on the whole US population, our study found that pre-diabetes was an independent risk factor for sarcopenia.…”
Section: Discussionsupporting
confidence: 46%
“…Few studies had been conducted to investigate the correlation between pre-diabetes and sarcopenia. A recent study conducted in Japan revealed increasing sarcopenia rate in pre-diabetic older men, but not women (21). Focusing on the whole US population, our study found that pre-diabetes was an independent risk factor for sarcopenia.…”
Section: Discussionsupporting
confidence: 46%
“…The role of gender, on the other hand, remains unclear in the literature. While in the cohort of this study, a relationship between LM and glycemic control was only obtained in women, there are other studies in which this relationship between T2D and SMM only appears in men [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 65%
“…
We read, with great interest, the recent article by Kaga et al, in which prediabetes was reported to be associated with sarcopenia in older men but not in older women based on the cross-sectional analysis using the baseline data from the Bunkyo Health Study. 1 This finding indicates that sarcopenia could have occurred prior to the onset of diabetes, particularly in older men, and highlights the need of conducting screening-oriented strategy for sarcopenia prevention in the aging population. However, in this article, several issues are worthy of discussion.First, as indicated in the Methods part, the authors performed separate analyses by sex for the association of glycaemic status with sarcopenia.
…”
mentioning
confidence: 80%